2022
DOI: 10.1002/glia.24173
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid signaling in glioma

Abstract: High-grade gliomas constitute the most frequent and aggressive form of primary brain cancer in adults. These tumors express cannabinoid CB 1 and CB 2 receptors, as well as other elements of the endocannabinoid system. Accruing preclinical evidence supports that pharmacological activation of cannabinoid receptors located on glioma cells exerts overt anti-tumoral effects by modulating key intracellular signaling pathways. The mechanism of this cannabinoid receptor-evoked anti-tumoral activity in experimental mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 121 publications
(185 reference statements)
1
20
0
Order By: Relevance
“…Taken together, we speculate that both CBD and CBG may induce cell differentiation due to their relatively stronger effects on GSCs via GPR55 signalling suppression that also suppresses GSCs stemness genes. This hypothesis must be further confirmed; however, it corroborates all previous studies on cannabinoids and CNR ligands that demonstrated GSC differentiation [ 12 , 13 , 14 ]; however, these studies did not mention the potential role of GPR55 ( Scheme 1 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Taken together, we speculate that both CBD and CBG may induce cell differentiation due to their relatively stronger effects on GSCs via GPR55 signalling suppression that also suppresses GSCs stemness genes. This hypothesis must be further confirmed; however, it corroborates all previous studies on cannabinoids and CNR ligands that demonstrated GSC differentiation [ 12 , 13 , 14 ]; however, these studies did not mention the potential role of GPR55 ( Scheme 1 ).…”
Section: Discussionsupporting
confidence: 85%
“…Kolbe et al [ 24 ] also reported highly variable expressions of CB1 and CB2 in primary GBM cells, observing low CNR2 gene expression but not always low CB2 protein expression. Over-expressed levels of specific CNRs are expected in all cancer cells [ 39 ] due to the well-documented high anticancer activity of the endogenous endocannabinoid system in the brain [ 13 , 40 ], which undoubtedly plays a role in glioma malignancy. For example, in GBMs expressing high CB1 level, CBD counteracted tumour growth also by inhibiting the endocannabinoid anandamide-degrading enzyme, thereby enhancing endocannabinoid activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the omnipresence what makes CB receptors a potential target for several pathologies [ 5 , 6 ]. In fact, CB receptors are expressed in a wide variety of cancers with different origin, such as glioma and melanoma, to name a few [ 7 , 8 ]. However, the role of these receptors is not yet very well understood.…”
Section: Introductionmentioning
confidence: 99%